Estudo da obtenção de nitreto de boro hexagonal por rotas de síntese assistidas por micro-ondas - Gaviria, Juan Pablo Yasnó (2018)
Boron nitride (h-BN) is an attractive ceramic material that combines excellent thermal, electrical and chemical properties. The combination of these properties makes h-BN useful in the manufacturing of lubricants, crucibles, cosmetics, electrical insulation and composites. The most widely used industrial methods for obtaining h-BN are carbothermal reduction of B2O3 and the reactions of H3BO3 and CH4N2O or C3H6N6 by conventional heating (resistive). However, they require prolonged reaction times and/or high temperatures, which in some cases makes it difficult to obtain nanoparticles. The importance of obtaining nanometric h-BN is the possibility of obtaining differentiated properties in potential applications such as UV light emitters, nanovectors in medicine, hydrogen storage and dielectric gates. In this context, this thesis studies the use of microwaves as an alternative source of heating in the three industrial methods of h-BN synthesis. The microwave synthesis resulted in the formation of h-BN in the three studied methods, revealing its potential in obtaining this material. The main highlight of using the microwaves in the studied synthesis was to obtain the phase-pure and crystalline h-BN nanoparticles in the method involving C3H6N6 with decreasing reaction time and temperature, when compared to conventional heating reported in the literature. The high heating rates provided by the microwaves obtained unprecedented results as: obtaining nanometric h-BN with a decrease in particle size, time and maximum reaction temperature of: 96%, 25% and 24%, respectively; and obtaining h-BN with a nanometric size similar to those of the literature, but with a decrease of time and maximum reaction temperature of 58% and 19%, respectively. The optical characterization of the h-BN synthesized by microwave confirmed the blue luminescence of the material, associated with native defects in its structure and with potential application in light emitters, displays and nanospectroscopy.